Development Of Computer-Based Photoshop Learning Media Using Computer Based Interaction Method - Muhammad Iqbal Panjaitan; Denni M Rajagukguk (Sean Institute, 2023)
Advances in communication and information technology need to be continuously adapted to various disciplines, including education. Nowadays, Photoshop is one of the most widely used editing software by designers to produce quality images. Factors that influence efforts to improve users' Photoshop learning abilities include teacher competence, learning facilities, learning environment, user learning motivation, and learning models used. To support Photoshop learning, it is necessary to design an attractive learning media. Computer-Based Instruction is one of the techniques commonly used to create a learning application, CBI is usually used for making interesting designs that apply human-computer interaction and how learning materials are made. And it can help users understand and further increase user enthusiasm and motivation to learn Photoshop. Macromedia Flash is a program used to design a learning application that describes the learning storyline. Photoshop CS 3 tutorial is designed using Macromedia Flash 8 which can be easily understood by users in the learning process.